The economic valuation of cultural heritage: An analysis of economics-based tools and their limitations - Dragouni, Mina (The Greek Review of Social Research, 2022)
In recent years, global neoliberal cultural policy promotes the idea of heritage as an “investment asset” pushing for the development of methods and tools for assessing the value of cultural heritage resources and monuments. In this framework, the paper explores some key concepts and techniques of mainstream economics that have been used so far in the extant literature to define and delineate heritage economic and societal value. As argued, although the value of monuments and the past is realised collectively through complex social processes, neoclassical economic methods are limited by capturing only a fragment of this value as defined by patterns of individual consumption. Given the need for a holistic approach to the subject, it is suggested that new methodologies are devised that firstly, combine economics tools with qualitative participatory research and secondly, are theoretically framed by broader concepts and questions of political economy that deviate from commons assumptions of microeconomics theory.